Pengembangan Kartu Unsur Periodik Kimia Berbasis Augmented Reality untuk Meningkatkan Motivasi Siswa dalam Belajar - Pradipta, Aruna (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
This research aims to describe the appearance of the KUPERKIM (chemical periodic element card) learning media and analyze the validation text results of the KUPERKIM learning media on periodic system of elements material. This research method uses the ADDIE method (analysis, design, development, implementation and evaluation). The validity test for the appropriateness of the material and media was carried out using 3 validators and the implementation test for the feasibility of using the media was carried out on 30 tenth grade students at MAN Insan Cendekia Siak as research samples using Likert scale indicators. The indicators contained in the media expert validation questionnaire include 15 indicators which are grouped into 2 aspects, include the software engineering aspect and the visual communication aspects. Apart from that, there are 15 indicators in the material expert validation questionnaire which are grouped into 4 aspects, including material aspects, linguistic aspects, implementation aspects, and visual communication aspects. Based on all assessments from media experts, the average score for all aspects is 3,35 and the assessment from material experts is 3.20, KUPERKIM can be declared suitable for use as an educational game media and can attract students’ interest in learning.